DEMAK-PASAI COLLABORATION IN THE ESTABLISHMENT OF JAKARTA: AN ARCHAEOLOGICAL ANALYSIS OF ACEH PASAI TOMBSTONES AT THE GREAT MOSQUE OF DEMAK - Arifia, Sariat; Mahdi, Mizuar; Akmal, Aslim; Munawir, Munawir; Adi, Jayanto A. (International Journal of Social Service and Research, 2024)
This study investigates the presence and significance of the Pasai tombstone typology in the Great Mosque of Demak, highlighting its archaeological significance as evidence of historical collaboration between Pasay and Demak in the 16th century to resist Portuguese colonization and establish the city of Jakarta. From all areas studied, 13 tombstones were found with the characteristics of the typology. The existence of this headstone in the cemetery area of the Demak Grand Mosque shows the connection between Demak Raden Trenggono and Pasais Fatahillah Against the Portuguese and the establishment of Jakarta is indeed an alliance between the two groups. This research explores the cultural and religious impact of the Wali Songo's religious and cultural teachings during the period of resistance against colonization, particularly in relation to their influence on the socio-political landscape of Java. In addition, oral histories and local narratives are collected that may shed light on the perceptions and legacies of Wali songo in the context of the resistance against Portuguese colonialism. This work enhances our understanding of regional interactions and cultural exchanges during a critical period in Southeast Asian history.